1996
DOI: 10.1016/s0006-8993(96)00326-5
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of lipopolysaccharide-induced fever by subdiaphragmatic vagotomy in guinea pigs

Abstract: It is generally believed that fever is mediated by certain cytokines produced by immune cells activated by exogenous pyrogens, e.g., lipopolysaccharides (LPS), released into the circulation and transported to the brain There, the cytokines are thought to stimulate prostaglandin (PG) E2 production within the organum vasculosum laminae terminalis region. PGE2 then may act as a febrigenic mediator locally or in the surrounding preoptic area (POA). However, whereas the increases in preoptic PGE2 and body (core) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
47
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 0 publications
6
47
1
Order By: Relevance
“…In summary, because the very early appearance of PGE 2 in IVC plasma coincides temporally with the onset of fever, these findings would support the notion that PGE 2 quickly elaborated by Kc stimulated by LPS-activated C could be the factor that stimulates vagal terminals in the liver or circulates to the brain and, hence, may be responsible for the prompt initiation of the febrile response to intravenous LPS, as postulated previously (6,22,43,49,50). This interpretation may also help to clarify the correlation between its elevation in plasma and the febrile course (35).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In summary, because the very early appearance of PGE 2 in IVC plasma coincides temporally with the onset of fever, these findings would support the notion that PGE 2 quickly elaborated by Kc stimulated by LPS-activated C could be the factor that stimulates vagal terminals in the liver or circulates to the brain and, hence, may be responsible for the prompt initiation of the febrile response to intravenous LPS, as postulated previously (6,22,43,49,50). This interpretation may also help to clarify the correlation between its elevation in plasma and the febrile course (35).…”
Section: Discussionsupporting
confidence: 83%
“…As cytokines are not constitutively expressed by Kc and their de novo production occurs after some delay (32), we and others have proposed, to account for the promptness of the febrile response to intravenous LPS, that the peripheral pyrogenic signal could be transmitted to the preoptic-anterior hypothalamic area (POA, the presumptive locus of the febrigenic controller) via a neuronal rather than a humoral mechanism (6). Thus evidence was adduced by us and others (12,49,59) that the vagus and its hepatic branch, in particular (52), may convey the pyrogenic signal to the brain. Indeed, IL-1␤ injected into the portal vein of anesthetized rats had been shown earlier to increase the electrical activity of the vagus (36).…”
mentioning
confidence: 93%
“…17,19 This was supported by data obtained on rats pretreated with small i.p. doses of capsaicin: the febrile response was suppressed, presumably due to widePerivagal capsaicin and fever 263 spread damage of C-fibers of the abdominal cavity.…”
Section: Discussionmentioning
confidence: 52%
“…doses of LPS were not influenced), 17,18 while other authors found much stronger inhibition of fever by vagotomy in a different species. 19 The effects were explained by destruction of vagal afferent fibers that were presumed to carry information mainly from the liver, at which place LPS is preferentially detoxified. 20,21 In contrast to this, the lack of effect of vagotomy on responses to larger LPS doses was thought to be due to other points of action: 22 any LPS exceeding the detoxifying capacity of the liver might induce febrigenic stimuli at either extrahepatic vagal fibers or other afferent nerves, or possibly at non-neuronal points.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular relevance in this regard are the findings that subdiaphragmatic vagotomy attenuates the LPS-and interleukin (IL)-1␤-induced increases in hypothalamic microdialysate NE (16,30,83,84) and NO (29). The febrile response to LPS (17,66,71,82,83) and the increase in LPS-induced preoptic PGE 2 (66; for review, see Ref. 6) have been shown previously to be similarly inhibited by subdiaphragmatic vagotomy.…”
mentioning
confidence: 93%